Are we speaking the industry language? The practice and literature of modernizing legacy systems with microservices - Colanzi, Thelma; Amaral, Aline; Assunção, Wesley; Zavadski, Arthur; Tanno, Douglas; Garcia, Alessandro; Lucena, Carlos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2021)
Microservice architecture has gained much attention in the last few years in both industry and academia. Microservice is an architectural style that enables developing systems as a suite of small loosely coupled, and autonomous (micro)services that encapsulate business capabilities and communicate with each other using language-agnostic APIs. Despite the microservice adoption for modernizing legacy systems, few studies investigate how microservices are used in practice. Furthermore, the literature still scarce on presenting studies on why and how the modernization is conducted in practice in comparison to existing literature on the subject. Thus, our goal is to investigate if industry and academy are speaking the same language concerning the modernization of legacy systems with microservices, by means of a rigorous study on the use of microservices in the industry. For doing so, we design a survey to understand the state of practice from the perspective of a modernization process roadmap derived from the literature. In this paper, we report the results of a survey with 56 software companies, from which 35 (63.6%) adopt the microservice architecture in their legacy systems. Results pointed out the most expected benefits that drive the migration to microservices are easier software maintenance, better scalability, ease of deployment, and technology flexibility. Besides, we verified, based on a set of activities defined in the modernization process, that the practitioners are performing their migration process according to the best literature practices.